The Impact of Aberrant Data Variability on Drug-Placebo Separation and Drug/Placebo Response in an Acute Schizophrenia Clinical Trial - Kott, Alan; Brannan, Stephen; Wang, Xingmei; Daniel, David (Schizophrenia bulletin open, 2021)
Objective: In the current posthoc analyses, we evaluated the impact of markers of aberrant data variability on drug placebo separation and placebo and drug response in an acute schizophrenia clinical trial. Methods: Positive and negative syndrome scale data were obtained from a phase 2, randomized, double-blind, placebo controlled trial in hospitalized adults with schizophrenia experiencing an acute exacerbation. We assessed the impact of a total of six markers of aberrant data variability: erratic ratings, unusually large postbaseline improvement, high and low mean square successive difference (MSSD), identical and nearly identical ratings and compared the drug placebo difference, drug and treatment response at last visit in affected subjects vs those not affected. All analyses were conducted using generalized linear models. Results: In this posthoc analysis, drug placebo separation decreased with the presence of most markers of aberrant data variability. The only exception was high MSSD was associated with significant increase in the signal. In the affected subjects, the presence of indicators of increased data variability augmented the response to placebo, in the case of large postbaseline change and high MSSD, significantly. The presence of indicators of decreased variability numerically but not statistically decreased the response to placebo. Similar findings were observed in the drug treatment group with the exception of erratic ratings that numerically but not statistically decreased the response to the drug. Discussion: The presence of most indicators of aberrant data variability had a detrimental effect on drug-placebo separation and showed different effects on placebo and treatment response.